FAKTOR-FAKTOR YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN PADA INVESTASI SAHAM (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Niswatul Amalia; Anik Malikah; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThis study aims to determine how much influence several factors have on decision making in stock investments. In this study there are 5 independent variables, namely investment knowledge, investment motivation, investment interest, information technology, investor behavior. And one dependent variable is stock investment decisions. The data used in this study are primary data, the population taken in this study were students of the Faculty of Economics and Business, Islamic University of Malang. Data collection techniques in this study using purposive sampling method. Tests used in this study are the f test, R2 test, and t test. The results in this study indicate that partially investment knowledge, investment motivation, investment interest, information technology, and investor behavior significantly influence stock investment decisions.Keywords: Investment Knowledge, Investment Motivation, Investment Interest, Information Technology, and Investor Behavior.